The intruder [compact disc, unabridged] - McFadden, Freida (Dreamscape Media, 2025)
Casey's cabin in the wilderness is not built for a hurricane, but she's a lot more worried about the girl she discovers lurking outside her kitchen window. She's young, alone, and covered in blood. The girl won't explain where she came from, or loosen her grip on the knife in her right hand. And when Casey makes a disturbing discovery in the middle of the night, things take a turn for the worse. The girl has a dark secret she'll kill to keep. And if Casey gets too close to the truth, she may not live to see the morning.